Hypoventilation in glycine-receptor antibody related progressive encephalomyelitis, rigidity and myoclonus. - Bourke, D; Roxburgh, R; Vincent, A; Cleland, J; Jeffery, O; Dugan, N; Abernethy, D; King, A; Anderson, N (2014)
Glycine receptor (GlyR) antibodies have been identified in patients with rigidity and hyperekplexia, but the clinical phenotype associated with these antibodies has not been fully elucidated. The clinical features in two additional patients with GlyR antibodies are described. A 55-year-old man presented with stimulus-induced hyperekplexia and rigidity in the lower limbs and trunk. He initially responded to benzodiazepines, but presented after 18 months with severe, painful, prolonged spasms associated with supraventricular and ventricular arrhythmias, hypoventilation and oxygen desaturation requiring intubation. He improved following treatment with clonazepam, baclofen and immunomodulatory therapies. A 58-year-old woman presented with stiffness in the legs and hyperekplexia associated with hypoventilation, at times leading to loss of consciousness. She responded to benzodiazepines and has remained in remission. The clinical picture associated with GlyR antibodies includes autonomic dysfunction, cardiac arrhythmias and hypoventilation. It is important to recognise these serious complications early to limit mortality from this treatable condition.